From Company Reputation to Environmental Performance. The Context of Corporate Social Responsibility Port Manager in Indonesia - MUAFI, MUAFI (Journal of Environmental Management and Tourism, 2018)
This study focuses on the influence of management commitment, service orientation and stakeholder role in affecting company reputation and environmental performance of State of Enterprises (SOE) in Indonesia. Some CSR managers in state-owned enterprises, especially in state-owned ports enterprise are facing problems about the complexity of allocating funds and CSR programs during field implementation. This study conducted on all managers of one largest port companies in Indonesia which is operating from Sumatra to Papua by using a mixed method. Data collection is done by giving questionnaire to all CSR managers throughout Indonesia and followed by interview and focus group discussion (FGD). Sampling technique is using purposive sampling. The results show that in order to improve the company reputation, company need to increase commitment, give excellent service orientation to the community, and establish a harmonious relationship with stakeholders. The service orientation to the community and the company reputation can improve environmental performance for companies who implement CSR and positively received by the community.